2021
DOI: 10.3389/fvets.2021.651369
|View full text |Cite
|
Sign up to set email alerts
|

PK/PD Modeling to Assess Rifaximin Clinical Dosage in a Mouse Model of Staphylococcus aureus-Induced Mastitis

Abstract: Staphylococcus aureus (S. aureus) is a common pathogen that causes mastitis, an infection of the milk-secreting tissue of the udder, in dairy cows, and presents a huge economic problem for the dairy industry worldwide. Thus, control and treatment of mastitis in dairy cows is vital in order to reduce the costs associated with the disease. The main purpose of the current work was to examine the current dosage of rifaximin for the treatment mastitis in cows caused by S. aureus using pharmacokinetic/pharmacodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…In our previous study, we administered rifaximin to one mammary gland of the fourth pair of mice, and the results showed that the drug concentration was not detected or close to the detection limit in the untreated mammary gland on opposite side [ 17 ]. Histologically, the close link between secretory cells at their apex by tight junctions in the lactating udder forms the blood–milk barrier, which accounts for the passive transport of drugs between the blood and milk [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, we administered rifaximin to one mammary gland of the fourth pair of mice, and the results showed that the drug concentration was not detected or close to the detection limit in the untreated mammary gland on opposite side [ 17 ]. Histologically, the close link between secretory cells at their apex by tight junctions in the lactating udder forms the blood–milk barrier, which accounts for the passive transport of drugs between the blood and milk [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mammary glands of the fourth pair are independent of each other and can be used as two independent samples for analysis. This method has been reported in our previous studies [ 17 ]. Four single-dose groups, with doses of 50, 100, 200, and 400 µg/gland, were used in the pharmacokinetics experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PK/PD indexes comprised the AUC/MIC (area under the time-concentration curve divided by MIC), %T > MIC (the percentage time for which the drug concentration exceeded MIC), and C max /MIC (peak concentration divided by MIC). The relationship between in vivo antibacterial effects (△log CFU/MG) and the PK/PD indexes were described using an inhibitory sigmoid E max model [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%